2022
DOI: 10.1186/s12906-022-03699-7
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine formula 01 for nasopharyngeal carcinoma (NPC01) for head & neck cancer and health-related quality of life: a retrospective study

Abstract: Background The traditional Chinese medicine (TCM) formula 01 for nasopharyngeal carcinoma (NPC01) is used in the management of head and neck cancers (HNCs), but whether NPC01 has an impact on the HR-QOL of patients with HNCs is unknown. Methods This was a retrospective study of patients with HNCs who were treated between January 2019 and January 2020 at the Head & Neck Cancer Center of Tianjin Medical University Cancer Institute & Hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Studies reported that Chinese medicine played a unique role in improving symptoms and quality of life (23)(24)(25). Significantly as the process of tumor development, when the tumor load gradually increases, the consumption of the host also gradually increases, and the quality of life in all aspects, such as emaciation, loss of appetite, fatigue, poor nutritional status, poor spirit, physical strength, and decreased activity tolerance 6…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that Chinese medicine played a unique role in improving symptoms and quality of life (23)(24)(25). Significantly as the process of tumor development, when the tumor load gradually increases, the consumption of the host also gradually increases, and the quality of life in all aspects, such as emaciation, loss of appetite, fatigue, poor nutritional status, poor spirit, physical strength, and decreased activity tolerance 6…”
Section: Discussionmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) is the state-of-the-art method of pinpoint radiation delivery due to recent advancements in radiation equipment and technology 1 . Previous studies [2][3][4][5][6] have shown a significant improvement in IMRT regarding tumor control and quality of life in NPC.…”
Section: Introductionmentioning
confidence: 99%